Landry Conrady: capstone - Conrady, Landry, artist (Colorado State University. Libraries, 2023)
The artist's statement: I have decided that my favorite thing about art is how it draws people together. Community is a substantial part of my life, and I have been able to see how good design and attractive aesthetics have the power to make people feel welcomed and engaged. The aim of my work is to utilize that power. Whatever the project - I just want people to feel welcomed after seeing each piece.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design